Tomato IPM in Florida - Stephanie Bloem; Russell F. Mizell (EDIS)
This document presents a historical narrative of tomato production in Florida that emphasizes the adoption and impact of Integrated Pest Management (IPM) practices and the future challenges facing tomato IPM research and technology transfer. This document is ENY-706, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: September 2001. Revised: March 2004.